Core–shell nanospheres to achieve ultralow friction polymer nanocomposites with superior mechanical properties. Issue 17 (12th April 2019) - Zhang, Lin; Ren, Yilong; Peng, Shiguang; Guo, Dan; Wen, Shizhu; Luo, Jianbin; Xie, Guoxin
Abstract : The mechanical and lubrication properties of the core–shell nanocomposite show great advantages over those of conventional composites prepared by mechanical mixing. Abstract : Core–shell nanospheres have been widely used in catalysis, batteries, medicine, etc . owing to their unique structural characteristics, which exhibit optimal performance and integrated functions of both the core and shell materials. To simultaneously achieve outstanding mechanical properties and remarkable lubrication properties in desirable polymer composites, core–shell nanospheres with polytetrafluoroethylene (PTFE) as the core and poly methyl methacrylate (PMMA) as the shell have been adopted as structural units to form bulk nanocomposites. We demonstrated that the mechanical and lubrication properties of the nanocomposites prepared using core–shell nanospheres as the continuous matrix were dramatically improved. Specifically, when compared with that of pure PTFE, the compressive strength of the PTFE@PMMA nanocomposite obviously increased up to one order of magnitude (from ∼9 to ∼90 MPa), the friction coefficient reduced to 25% (the lowest value was 0.03), and the wear rate decreased up to two orders of magnitude. Moreover, the mechanical and lubrication properties of the nanocomposites could be adjusted by changing the core–shell ratio, and an appropriate core–shell ratio was beneficial for achieving the desired comprehensive properties. It has been proposed that the properties, such as the confinement effect, improved dispersion capacity, etc ., imparted by the core–shell structure effectively lead to high dispersion of the reinforcement phase, improvement of the binding force of the transfer film to the friction surface, and interruption of the wear process of the polymer composite.